The Role of the Customs Department in the Protection of Intellectual Property - Ben Taibi, Mobarek; Bellaoui, Abdelkader (Journal of Legal Studies and Researches, 2020)
The Customs Department, by virtue of its strategic location, applies many laws and regulations to the application of the Customs Law, and the legislator has assigned it to the suppression of various crimes on the border, including offenses of infringement of intellectual property, through a series of special customs measures. Through this study, we highlight the various methods and mechanisms of customs administration intervention to address all forms of counterfeiting and infringement of intellectual property rights and their effectiveness, especially administrative and procedural measures during customs disputes related to intellectual property rights.